Correlating spectral and timing properties in the evolving jet of the microblazar MAXI J1836−194. Issue 4 (24th December 2020) - Lucchini, M; Russell, T D; Markoff, S B; Vincentelli, F; Gardenier, D; Ceccobello, C; Uttley, P
ABSTRACT: During outbursts, the observational properties of black hole X-ray binaries vary on time-scales of days to months. These relatively short time-scales make these systems ideal laboratories to probe the coupling between accreting material and outflowing jets as the accretion rate varies. In particular, the origin of the hard X-ray emission is poorly understood and highly debated. This spectral component, which has a power-law shape, is due to Comptonization of photons near the black hole, but it is unclear whether it originates in the accretion flow itself, or at the base of the jet, or possibly the interface region between them. In this paper, we explore the disc–jet connection by modelling the multiwavelength emission of MAXI J1836−194 during its 2011 outburst. We combine radio through X-ray spectra, X-ray timing information, and a robust joint-fitting method to better isolate the jet's physical properties. Our results demonstrate that the jet base can produce power-law hard X-ray emission in this system/outburst, provided that its base is fairly compact and that the temperatures of the emitting electrons are subrelativistic. Because of energetic considerations, our model favours mildly pair-loaded jets carrying at least 20 pairs per proton. Finally, we find that the properties of the X-ray power spectrum are correlated with the jet properties, suggesting that an underlying physical process regulates both.